2011
DOI: 10.1007/s00066-011-4002-z
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of female pelvic malignancies regarding MRI, CT, and PET/CT

Abstract: MRI is a useful additional diagnostic complement but by no means replaces established methods of gynecologic diagnostics and ultrasound. In fact, MRI is only implemented in the guidelines for vulvar cancer. According to the current literature, CT is still the cross-sectional imaging modality of choice for evaluating ovarian cancer. PET/CT appears to have advantages for staging and follow-up in sarcomas and cancers of the ovaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Tumour, however, will be hyperintense on T 2 and enhance early and avidly (Figure 8). 77 When recurrence is suspected more than 6 months after treatment, MRI readily differentiates between scar tissue and cancer; by this point, radiation-induced oedema should have resolved. A previous study by Ebner et al 52 suggested that distinction between fibrosis and recurrent disease can be made solely on T 2 weighted imaging at 12-18 months after treatment (Figures 8 and 9).…”
Section: Treatment Of Vaginal Cancer Is Guided By the Figo Stage And mentioning
confidence: 99%
“…Tumour, however, will be hyperintense on T 2 and enhance early and avidly (Figure 8). 77 When recurrence is suspected more than 6 months after treatment, MRI readily differentiates between scar tissue and cancer; by this point, radiation-induced oedema should have resolved. A previous study by Ebner et al 52 suggested that distinction between fibrosis and recurrent disease can be made solely on T 2 weighted imaging at 12-18 months after treatment (Figures 8 and 9).…”
Section: Treatment Of Vaginal Cancer Is Guided By the Figo Stage And mentioning
confidence: 99%
“…19,6,20 Furthermore, the positive impact of GEC-ESTRO Recommendations of image-guided BT (IGBT) with repetitive MRI in clinical practice, which gained a worldwide impact, 21,22 with MRI superiority to CT and clinical examination in the appreciation of the local tumor extension and in the evaluation of the parametrial involvement, the use of MRI is considered the "Gold Standard" for IGBT. [23][24][25][26][27][28][29] Another technique that can be used for the evaluation of the tumor dimensions in the cervical cancer is TRUS. Zaritzky et al were the first to apply TRUS in gynecology.…”
Section: Fig 2 -The Linear Regression Analysis For the (A) Tumor Widmentioning
confidence: 99%
“…There are a few reports suggesting that these tumors are FDG avid and that PET/CT can be used for staging them, however there is very little published data addressing the diagnostic impact of PET/CT in vulvar and vaginal cancers [12]. Thus, the purpose of this study was to evaluate the changes in prognostic impression and patient management following PET/CT in patients with vulvar and vaginal carcinoma; and to compare the PET/CT findings with those of conventional imaging modalities.…”
Section: Introductionmentioning
confidence: 99%